Digestive cancer seen from the dynamics: flat lesions of the gastrointestinal mucous and dysplasia - Romero Madero, Jesús; Bello Núñez, Milay (Revista 16 de abril, 2018)
The digestive cancer takes an important place in the world mortality and in our country too. The sequence metaplasiadysplasia-adenoma at histological level constitutes a model which can be considered the precursor of the someone, being involved the flat adenomas accompanied by a certain progressive dysplasia grade more and more in this relationship. With the objective of to contribute to the couple's upgrade deep knowledge: flat lesions-dysplasia of the gastrointestinal tract and their linking with the digestive cancer it was carried out an exhaustive bibliographical revision. The employment of novel technical endoscopic image and digestive respective tints of them have allowed to improve the diagnostic yield of the digestive flat lesions and it source of new classifications to have a conception but it completes and integral of the dynamics: premalignant digestive injure -cancer, being necessary to understand the dynamics of the aspects macros (endoscopic aspects ) and micros (histological aspects) of the couple: flat lesionsdysplasia and ulterior evolution in the patient. The couple's deep knowledge: flat lesions-dysplasia, can constitute one of the medullary factors in the most precocious detection in the cancer of digestive origin.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />